2018
DOI: 10.1038/s41398-018-0099-5
|View full text |Cite
|
Sign up to set email alerts
|

A GABAergic cell type in the lateral habenula links hypothalamic homeostatic and midbrain motivation circuits with sex steroid signaling

Abstract: The lateral habenula (LHb) has a key role in integrating a variety of neural circuits associated with reward and aversive behaviors. There is limited information about how the different cell types and neuronal circuits within the LHb coordinate physiological and motivational states. Here, we report a cell type in the medial division of the LHb (LHbM) in male rats that is distinguished by: (1) a molecular signature for GABAergic neurotransmission (Slc32a1/VGAT) and estrogen receptor (Esr1/ERα) expression, at bo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
108
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 92 publications
(109 citation statements)
references
References 83 publications
1
108
0
Order By: Relevance
“…Therefore, any of these regions may drive Fs‐mediated inhibition. Another possibility is that a recently described population of GABAergic interneurons in the medial LHb promotes the inhibition after shock, although such functional connectivity remains to be demonstrated (Zhang, Hernández, Vázquez‐Juárez, Chay, & Barrio, ; Zhang, Hernánde, et al., ; Zhang, Shen, et al., ). Finally, the block of Fs‐excitation or Fs‐inhibition by pharmacological agents revealed pure excitatory or inhibitory responses.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, any of these regions may drive Fs‐mediated inhibition. Another possibility is that a recently described population of GABAergic interneurons in the medial LHb promotes the inhibition after shock, although such functional connectivity remains to be demonstrated (Zhang, Hernández, Vázquez‐Juárez, Chay, & Barrio, ; Zhang, Hernánde, et al., ; Zhang, Shen, et al., ). Finally, the block of Fs‐excitation or Fs‐inhibition by pharmacological agents revealed pure excitatory or inhibitory responses.…”
Section: Discussionmentioning
confidence: 99%
“…Hypothalamic glutamatergic signal into the LHb is necessary to trigger LHb excitation and promotes innate escape behaviour (Lecca et al., ). Similarly, other glutamatergic inputs also drive aversive behaviours (Barker et al., ; Knowland et al., ; Shabel et al., ; Zhang, Hernánde, et al., ; Zhang, Shen, et al., ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have described the LHb as consisting almost exclusively of glutamate projection neurons expressing vesicular glutamate transporter 2 (vGlut2) 21 . However, there is recent histological and single-cell sequencing evidence that the LHb contains a small population of cells that express glutamate decarboxylase 2 (GAD2) [22][23][24][25] , which is generally a marker of GABAergic inhibitory neurons. Despite these recent studies, very little is known about GAD2 neurons in the LHb, including which inputs target them or whether they are capable of providing local inhibition, long-range inhibition, or both.…”
Section: Main Textmentioning
confidence: 99%
“…Despite these recent studies, very little is known about GAD2 neurons in the LHb, including which inputs target them or whether they are capable of providing local inhibition, long-range inhibition, or both. Recent studies have reported that they are enriched in receptors for a number of hypothalamic-derived neuropeptides and hormones, including orexin receptor 2 (OxR2) 23,25 . As orexin neuron cell bodies are located solely in the lateral hypothalamus (LH) 26 , this suggests that LHb GAD2 neurons are modulated by projections from lateral hypothalamic orexin neurons.…”
Section: Main Textmentioning
confidence: 99%